Leakage Detection in Underground Gas Pipeline - Kishor Kale, Renuka; Nalbalwar, S. L.; Deosarkar, S. B.; Singh, Sachin (International Journal of Computer Sciences and Engineering, 2019)
The pipeline system is the most important part in media transport in order to deliver fluid to another station. The weak maintenance and poor safety will directly lead to financial losses in term of fluid waste, destruction of human race, animals, birds and causing environmental impacts by leaving large amount of unwanted gases in the ecosystem. There are many classifications of techniques to make it easier to show their specific method and application. In this paper we will discuss about the problem faced by Maharashtra Natural gas Ltd (MNGL) and Mahanagar Gas. The motive is to find the leakage is at what percent as these Navratna‟s uses Compressed natural gas (CNG), Liquefied petroleum gas (LPG) and Piped Gas and what is the flow rate of Leakage as well as we can monitor the health of the system. We have developed a system wherein Flow Rate, Temperature, Fire, Gas are the parameters of Inspection. A design is developed using Slave 1 and 2 for demonstration purpose on LCD display also using Internet of Things platform for easy receving data formats, and a html webpage is prepared to read the values in Tabular context. Discoveries dependent on the this IOT strategy can be utilized for near investigation in the future. It‟s the best technique to recognize spill in gas pipelines. More analysis and reproduction should be completed to get the quick consequence of spilling and estimation of their area.